Analysis of definitive chemo-radiation outcomes in anal cancer: insights from a tertiary cancer center in the MENA Region - Tala Alawabdeh; Ramiz Abuhijlih; Issa Mohamed; Saif Alnasraween; Hazem Ababneh; Reem Turfa; Sanad Alsunna; Yacoub Khzouz; Fawzi Abuhijla (Frontiers in Oncology, 2024)
BackgroundOutcomes of chemo-radiation (CRT) for anal cancer in Middle East and North Africa (MENA) are scarce. We aim to report treatment outcomes for anal cancer treated at tertiary cancer center, with a particular focus on patients managed with non-oncological surgery prior definitive CRT.MethodsWe conducted a retrospective review of patients diagnosed with locally advanced anal carcinoma, who underwent definitive CRT King Hussein Cancer Center, from January 2007 till January 2020. Patient demographics and disease characteristics were extracted, and a univariate chi-squared test was employed to assess the impact of chemotherapy type, HPV status, and pre-treatment non-oncological surgery on outcomes, including complete remission (CR), disease-free survival (DFS), and overall survival (OS). Kaplan–Meier tests were employed to analyze the obtained survival data.ResultsAmong the 34 initially identified patients, 30 were eligible, 24 (80%) achieved CR. Notably, 20 out of 21 HPV positive patients achieved CR, versus 1 out 4 HPV-negative achieved CR, p=0.006The 5-years OS for HPV-positive patients was 89% compared with 25% for HPV-negative, p=0001. There was no statistical significant difference in patients outcomes as regard type of chemotherapy, radiation technique and non-oncologic resection prior to CRT.ConclusionHerein, we reported the first series of anal cancer from our region. CRT had yielded an oncologic outcome comparable with series in the literature. HPV-positive patients demonstrated better results. Moreover, we found non-oncologic resection prior to CRT did not seem to impact the outcomes. Further studies are warranted to overcome the limitations of our study.